Pengembangan Bahan Ajar Lembar Kerja Siswa (LKS) Materi Lingkaran dengan Pendekatan Investigasi Kelas VIII SMP (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2020)
This study aims to design and produce teaching materials in the form of mathematics learning worksheets with an investigative approach to circle material. The research used is Development Research. The development of this circle material is carried out following two main stages of development research, namely the preliminary study stage (preparation stage, model development (design) stage) and formative evaluation stage which includes prototyping (self evaluation, expert review, one-to-one, and small group). and field tests. The subjects in this study were students of class VIII at SMP Negeri 41 Palembang as many as 40 students. In this study, the data collection techniques used were documentation, walkthroughs, and learning outcomes tests. Based on the results of the study, students who graduated with scores above the KKM were 81.58% with a total of 31 students, which means that the developed worksheets have a potential effect on student learning outcomes.